THE IMPORTANCE OF HYDROTHERAPY IN THE REHABILITATION OF SEQUELS IN NEUROLOGICAL PATIENTS - Mendes Pereira Barbosa, Daniela; Fonceca Pimenta, Stéfani (Health and Society, 2023)
Introduction: The neurological sequelae are result from the brain damages occasioned by pathologies that affect the central nervous system and/or peripheral nervous system resulting in malfunction, limitations and physical and/or cognitive incapacities. Among the resulting sequels from the brain damages are found the muscle weakness, hypertonia, hypotonia, limited range of motion, difficulty transferring and walking, sensory loss, incoordination and postural instability. The hydrotherapy is a specialty of aquatic physiotherapy that uses water in all its states, as a treating agent of injuries and physical conditions. It will act in the rehabilitation of these patients promoting a greater evolution of themselves due to the facilitations given by the aquatic environment during the exercises which will entail in respiratory, cardiovascular, musculoskeletal and psychological benefits. Objective: To analyze hydrotherapy in the rehabilitation of sequelae in neurological patients. Method: It was performed a file search in the Scielo (Scientific Eletronic Library On-line), Google Scholar and PubMed database in the English and Portuguese languages. Bibliographic research bases were also used. Conclusion: Based on the surveys investigated, it was found that the use of hydrotherapy in the rehabilitation of neurological sequelae was extremely favorable in the recovery of patients, providing a significant improvement and a superior evolution to the traditional treatments performed on the ground.